Rethinking development: India's cultural ethos as foundation - Mathur, B.P. (2019)
According to the development model India has adopted, development is viewed in narrow terms of economic development and, more particularly, GDP growth. This is largely due to our blind imitation of Western philosophy, which is based on materialistic values, and has given birth to current ruling economic ideology of free markets and competition, where earning money and accumulating wealth is considered primary goal of life. In its practical operation, this model creates serious socio-economic problems, such as ecological devastation, economic inequality, culture of consumerism, unemployment and social Darwinism. In India today, most components of social and economic well-being of people, such as education, health, employment and a healthy agricultural and industrial base, are in dismal state, indicating that our existing policy has failed. This calls for a fundamental rethink of our development policy. There is a need to embrace a more human-centric model of development, based on our cultural and civilisational ethos, which is ethico-spiritual and is deeply concerned with the problem of human welfare, social good and well-being of people. There is a need to redefine our development goals as creation of a happy, healthy and prosperous society. - Reproduced.
Keywords: Culture - India